Shame Travels - Sanghera, Jasvinder (London Hodder & Stoughton, 2012)
Jasvinder Sanghera, international bestselling author of Shame, describes her life-changing journey to the rural Punjabi village of Kang Sabu - the village where her parents grew up.
When she was a little girl, Jasvinder Sanghera's father told her about the village he came from, Kang Sabhu in rural Punjab. One day, he promised to take her there so she could meet her half-sister, Bachanu, who had stayed behind. But at the age of sixteen - as she so vividly related in her bestseller Shame - Jasvinder ran away from home to escape a forced marriage. Her parents disowned her. 'Shame travels...' her father told her. Although her mother took all her other daughters to meet the extended family in the Punjab, Jasvinder was never allowed to go. With her own daughter about to marry, Jasvinder decides to challenge thirty years of rejection by going to India herself. She wants to explore her roots and to see for herself the place her parents called home until the day they died. What Jasvinder finds in India and what she learns changes the way she sees the world, and has important lessons for all of us. SHAME TRAVELS is not only a gripping and revealing quest, but also an inspirational journey of the heart.
Include Appendix and Illustrations.
Keywords: Manners and customs -- India--Punjab -- Sanghera, Jasvinder -- Families